2019
DOI: 10.5796/electrochemistry.19-6-e2676
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Applications of Redox Enzyme-functionalized Electrode Reactions

Abstract: Electrochemical coupling of redox enzyme reactions, called bioelectrocatalysis, has been attracting great attention over the last four decades. It has become an important technology that can be applied to a wide range of bioelectrochemical devices including biosensors, biofuel cells, and bioreactors. This article presents an overview of the basic concepts of steady-state catalytic waves of mediated-and direct electron transfer (DET)-type bioelectrocatalysis. Several equations that can be used for the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 103 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…However, as the difference between the two redox potentials (driving force of the reaction) becomes larger, the reaction rate constant between the enzyme and the mediator becomes exponentially higher according to the linear free energy relationship. 42 Thus, before the potential-independent region, the positive shift of redox potential of the mediator would lead to a higher reaction rate between the enzyme and the mediator. The output current would be higher at the expense of higher overpotential.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the difference between the two redox potentials (driving force of the reaction) becomes larger, the reaction rate constant between the enzyme and the mediator becomes exponentially higher according to the linear free energy relationship. 42 Thus, before the potential-independent region, the positive shift of redox potential of the mediator would lead to a higher reaction rate between the enzyme and the mediator. The output current would be higher at the expense of higher overpotential.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nanostructured electrodes with a large ratio of the effective surface area against the projective surface area are useful and frequently utilized for bioelectrocatalytic systems. In addition, it is suggested that the heterogeneous electron transfer kinetics at the top edge of the microstructures of these electrodes is accelerated by the electric field strengthened by the expansion of the electric double layer [56] and the charge accumulation as expected by the Poisson equation [4]. This effect is very useful to decrease the overpotential due to the heterogeneous electron transfer in the DET-type reaction.…”
Section: Electrode Nanomaterialsmentioning
confidence: 98%
“…The coupled reaction is called bioelectrocatalysis, and the catalytic function of the redox enzymes provides a variety of specific and strong catalytic activities to nonspecific electrode reactions. [1][2][3][4][5]. Bioelectrocatalysis provides a firm base for characterizing redox enzyme reactions and applying the concept and related technologies to useful bioelectrochemical devices such as biosensors [6][7][8][9][10][11][12][13][14], biofuel cells [11,[15][16][17][18][19][20][21], biosupercapacitors [22], and other bioreactors [23].…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of redox enzymatic reactions with electrochemical reactions has received worldwide medical and scientific interests [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The coupled reaction is called bioelectrocatalysis.…”
Section: Introductionmentioning
confidence: 99%